Vehicles of Meaning: Ships, Materiality, and the Boundaries of the Iliad - Ward, Matthew George (Trinity College Dublin. School of Histories & Humanities. Discipline of Classics, 2022)
Ships are the most prominent material objects in the world of epic and the lemma ship (νηῦς) is the one of the most common substantives in the Iliad. Despite this, there has never been a sustained account of what ships do in the poem beyond either questions of archaeological construction or metrical quantification. This thesis addresses that gap, and is the first attempt to consider the literary role and function of ships in the Iliad. I argue that ships are significant material objects that help to articulate key structures of narrative, temporality, space, and the relational axes of ethnicity, politics, gender, theology, and ethics in the poem s discursive universe. To make this argument, this thesis draws on the emerging attention to objects as part of the material turn and in the New Materialisms in particular. I practice a philology of things to argue that ships are prevalent and significant material objects that enact, encode, and structure the organising systems of the Iliadic world. To say something about ships is thus to say something about the Iliad itself. The first chapter ( Time ) argues that ships help to articulate the temporality of the Iliad and those within it. Ships are polychronic, multitemporal objects that materialise the interconnection of the past, present, and future in a poem of the past that looks ahead to the fall of Troy and its memory to come. The second chapter ( Space ) reads the ships of the Iliad as heterotopic entities that both demarcate and problematise the spatial boundaries of the poem. As vehicles that move, ships implicate other spaces within the Iliad as they construct a narrative space that is a porous network of political and social relationships. The third chapter ( Gods ) argues that ships materialise the difference between mortals and immortals in epic. No god goes in a ship in the Iliad, and as a result ships are crucial material objects that express and interrogate the limits of the mortal world against the backdrop of the divine. The fourth chapter ( Women ) argues that ships play an important role in the constitution of gender hierarchies of the Iliad. Ships construct the differences between the male and female spheres of the poem men sail ships, women do not and as a result help to articulate the plurality of female subject positions that produce and affect the diverse array of women in the Iliad. The fifth and final chapter ( Men ) explores the way in which ships materialise the economy of κλέος and struggles for status that are central to the male world of the poem. Men come in their ships to fight and win the symbolic capital that offers a path to immortality in song, but success for one man means death and loss for others. Ships help to articulate the intertwining of celebration and destruction in the Iliad s complex interrogation of male heroism. This thesis aims to offer a new interpretation of an under-recognised phenomenon in the Iliad, and, therefore, a new framework for reading the poem itself. Ships, I argue, are a productive interpretive prism that expose the broad spectrum of the poem s conceptual underpinnings. What is an ostensibly inanimate background object can improve our understanding of significant structures of time, space, societal dynamics, and mortality in Homer s poetry.
APPROVED
Keywords: Iliad, Ships, Homer, Materiality, Philology of Things